Microanatomical Structure and Physical Characteristics of Thin Tail Hogget with Calpastatin (CAST-1) Genotype Differences - B W Putra; C Sumantri; . Nurhidayat (Faculty of Animal Science, Bogor Agricultural University, 2013)
Thin tail sheep has good adaptation in tropics condition, but they have low meat quality. Quality of thin tail hogget can be improved by selection. Calpastatin (CAST) gene is an indigenous inhibitor of calpain that involved in regulation of protein turn over and growth. The objective of this research was to determine the effect of calpastatin-genotype on microanatomical structure and physical characteristics of thin tail hodget. Nine thin tail sheep from Jonggol were used for this research.PCR-RFLP method was carried out to identify genetic variation of calpastatin gene, based on the identificationof CAST variation genotype. It was found that MM and MN genotypes forcalpastatin gene with TT as asingle Calpain genotype variation. The sheep wasclustered based on the variation of calpastatin gene, 5 sheep hadMM genotype and 4 sheep hadMN genotype. Physical and microanatomical characteristics were analyzed from their meats. Sheep with MN genotype showed tougher meat, it was characterized with a greater of muscle fiber surface area, the number of muscle per muscle bundle and muscle bundle area and harder meat tenderness than in MM genotypes. Hypertrophy and hyperplasia of MN were greater than MM.